Educação Moral e Cívica na ditadura militar : um estudo de manuais didáticos - Almeida, Djair Lázaro de (2016)
The purpose of this essay is to investigate, through the analysis of didatic manuals, the meaning of the subjects Moral and Civic Education and Brazil s Social and Political Organization during Brazil s military dictatorship post 1964. This analysis was completed with school writing register studies. To understand the discussion which drove the educational policy during the military dictatorship, 20 didactic manuals and their references were analyzed. Used as a primary source, the material served to point out specific arguments attributed to military rule. These arguments were submitted in this work to the materialist conception of history. In an attempt to reveal the influence of the named manuals as supporting arguments in accordance with the military regime, an attempt to understand how the persuasive reasonings became joined to the ideological justifications from the institutional discourse. In this process, new disciplines (or subjects), reorganizing existing moral and civic values, were used as support for the national mystic returned to the security and development binomial. It was then shown the authoritarian position of the moral and civic education during the military regime further proving how students were instructed through the use of stereotypes and idealizations.